Destination Image Mediated by Tourists’ and Resident Visitors’ Experience Quality -Empirical Evidence from Qingzhou, China - Liping, Guan (unpublished, 2024)
The destination image is a critical aspect for destinations. Typically, destination image is considered as a combination of cognition and affection. As tourists increasingly seek the quality of experience, this study proposes experience quality as a mediator between cognition and affection in the destination image framework based on previous studies. The proposed integrated destination image model was empirically studied in Qingzhou city, China, from the perspectives of tourists as well as resident visitors since they are both the primary consumers for pleasure in the destination. Furthermore, the results on cognition, experience quality, affection, and the image of a destination of Qingzhou was juxtaposed across the two groups. Lastly, this study adopted importance performance approach to provide a practical recommendation to the areas to be improved by the tourism operators in destination of Qingzhou. Quantitative method was used in this study. A structured survey was conveniently sampled on both tourists and residents in Qingzhou, resulting in 475 tourist respondents and 542 resident respondents after data cleaning. In the first step of data analysis for tourists and residents, exploratory factor analysis (EFA) was used to determine the dimensions and simplify the measurement. Confirmatory factor analysis (CFA) was then employed to check the construct’s unidimensionality, validity, and reliability. In the second step, a disjoint two-stage approach in PLS-SEM, which involves testing higher order constructs (HOCs), was used in each of the two groups. The first stage assessed the reliability and validity of the measurement model as for the reflective measurement and HOCs. And then in the second stage of structural model assessment, experience quality was satisfactorily found to be a mediator between cognition and affection. In the third step, multi-group analysis (MGA) was used to test if the two pre-defined data groups had any significant differences in their group-specific parameter estimates. The two groups were found to have the same three cognition dimensions, with each covering the same attributes (by EFA and CFA), showing configuration invariance. A permutation test was conducted to confirm partial measurement invariance, and the result of MGA revealed that path coefficients/effect differences were not statistically significant. In the fourth step, importance-performance map analysis (IPMA) was used to extend the results of PLS-SEM by considering the relative importance of constructs in explaining other constructs, as well as their performance. In IPMA, we go further to analyse the indicator level to help practitioners be more precise in their practices.Overall, this empirical study in Qingzhou made theoretical contributions by providing a better understanding of well accepted cognition-affection-destination image model, by highlighting the mediating role of experience quality between cognition and affection in the destination image model and by verifying the applicability of the proposed destination image model to resident visitors apart from tourists. It also provides managerial implications to destination operators in Qingzhou by development of recommendations on where should be improved to enhance visitors' experience quality and destination image perception. Furthermore, the well-designed methodological flow can benefit the scale construction to measure the highly specific image perception of a destination. However, the study has some limitations which leave room for future research such as incorporating more stakeholders, categorizing the destination image model based on the destination’s life cycle, etc.